Analytical investigation of peristaltic nanofluid flow and heat transfer in an asymmetric wavy wall channel (Part I: Straight channel). (November 2018) - Mosayebidorcheh, S.; Hatami, M.
Graphical abstract: Highlights: Two-dimensional peristaltic nanofluid flow in an asymmetric channel is modeled. Both upper and lower channel walls are considered in a wavy shape. Least Square Method (LSM) is introduced as efficient analytical method for solution. The effect of some parameters are discussed on results. Abstract: In this study, asymmetric peristaltic nanofluid flow in a two dimensional wavy channel is modeled and the heat transfer analysis is performed for it. Both upper and lower channel walls are considered in constant temperature and wavy shape. The governing equations were solved for five type's nanofluids and least square method (LSM) analytical method using the Maple 15.0 mathematical software is applied as the efficient solution method for solving the governing equation. The effect of some parameters existed in the equations (Brinkman number, thermal and velocity slip parameters, Grashoff number and etc.), are discussed on the velocities and temperature functions. As an important outcome, reverse flow and maximum velocity were observed in channel throat and maximum temperature area occurred near the lower wall due to its higher temperature in boundary condition. Also, Brinkman number, thermal slip parameter and Grashoff number increments enhanced the temperatures values in channel.